Course and Predictors of Major Depressive Disorder in the Canadian Armed Forces Members and Veterans Mental Health Follow-up Survey: Cours et Prédicteurs du Trouble de Dépression Majeure Dans l'Enquête de Suivi Sur la Santé Mentale Auprès Des Membres des Forces Armées Canadiennes et des ex-Militaires. (November 2021) - Enns, Murray W.; Mota, Natalie; Afifi, Tracie O.; Bolton, Shay-Lee; Richardson, J. Don; Patten, Scott B.; Sareen, Jitender
Objectives: The present report is the first study of Canadian military personnel to use longitudinal survey data to identify factors that determine major depressive episodes (MDEs) over a period of 16 years. Methods: The study used data from the Canadian Armed Forces Members and Veterans Mental Health Follow-up Survey (CAFVMHS) collected in 2018 ( n = 2, 941, response rate 68.7%) and linked baseline data from the same participants that were collected in 2002 when they were Canadian Regular Force members. The study used structured interviews to identify 5 common Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition mental disorders and collected demographic data, as well as information about traumatic experiences, childhood adversities, work stress, and potential resilience factors. Respondents were divided into 4 possible MDE courses: No Disorder, Remitting, New Onset, and Persistent/Recurrent. Relative risk ratios (RRRs) from multinomial regression models were used to evaluate determinants of these outcomes. Results: A history of anxiety disorders and post-traumatic stress disorder (RRRs: 1.50 to 20.55), mental health service utilization (RRRs: 1.70 to 12.34), veteran status (RRRs: 1.64 to 2.15), deployment-associated traumatic events (RRRs: 1.71 to 2.27), sexual traumas (RRRs: 1.91 to 2.93), other traumas (RRRs: 1.67 to 2.64), childhood adversities (RRRs: 1.39 to 1.97), avoidance coping (RRRs 1.09 to 1.49), higher frequency of religious attendance (RRRs: 1.54 to 1.61), and work stress (RRRs: 1.05 to 1.10) were associated with MDE courses in most analyses. Problem-focused coping (RRRs: 0.73 to 0.91) and social support (RRRs: 0.95 to 0.98) were associated with protection against MDEs. Conclusions: The time periods following deployment and trauma exposure and during the transition from active duty to veteran status are particularly relevant for vulnerability to depression in military members. Interventions that enhance problem-focused coping and social support may be protective against MDEs in military members.